Enhancing Distance Learning through Immersive Technologies: Integration of Augmented and Virtual Reality in Higher Education - Shofiyuddin, Ahmad; Choiri, Muttaqin; Setiawan, Firman; Utsman, Ahmad Farid; Azmi, Ahmad Rifqi (Journal of Islamic Education Research, 2025)
This study investigates the integration of Augmented Reality (AR) and Virtual Reality (VR) in distance learning to enhance student engagement and comprehension in higher education. Employing a Research and Development (R&D) design guided by the ADDIE model, the research was conducted at four Indonesian universities. In the analysis stage, data were gathered from students and lecturers to identify learning challenges. Based on this, AR/VR-based modules were designed and implemented, particularly in zakat-related subjects. The results showed significant improvements in student motivation and understanding, with post-intervention test scores rising notably. Students experienced a more immersive and interactive environment, enabling flexible and context-rich learning. The study also highlights the importance of faculty training, infrastructure readiness, and continuous evaluation to ensure successful implementation. Findings support theories such as Dual Coding, Experiential Learning, and Constructivism, indicating that AR and VR can transform distance learning into more effective, inclusive, and student-centered experiences. Penelitian ini mengkaji integrasi teknologi Augmented Reality (AR) dan Virtual Reality (VR) dalam pembelajaran jarak jauh untuk meningkatkan keterlibatan dan pemahaman mahasiswa di pendidikan tinggi. Menggunakan pendekatan Research and Development (R&D) dengan model ADDIE, studi ini dilakukan di empat perguruan tinggi Indonesia. Pada tahap analisis, data dikumpulkan dari mahasiswa dan dosen untuk mengidentifikasi tantangan belajar. Modul berbasis AR/VR dikembangkan dan diterapkan, khususnya pada materi zakat. Hasilnya menunjukkan peningkatan signifikan dalam motivasi dan pemahaman siswa, dengan skor tes pasca-intervensi yang meningkat. Teknologi ini menciptakan lingkungan belajar yang imersif dan interaktif, memungkinkan pembelajaran yang lebih fleksibel dan kontekstual. Studi ini juga menekankan pentingnya pelatihan dosen, kesiapan infrastruktur, dan evaluasi berkelanjutan untuk keberhasilan implementasi. Temuan mendukung teori Dual Coding, Pembelajaran Pengalaman, dan Konstruktivisme, menunjukkan bahwa AR dan VR dapat mentransformasi pembelajaran jarak jauh menjadi lebih efektif, inklusif, dan berpusat pada siswa.